(untitled) (African Journal of Biomedical Research, 2022)
Peripheral arterial disease (PAD), a reflection of systemic atherosclerosis, is a clinical condition that manifest as atherosclerosis of the lower limb. The study determined the association among PAD, peripheral neuropathy (PN), and insulin resistance (IR) in patients with type 2 diabetes mellitus (T2DM). A cross-sectional study was conducted among patients with T2DM attending the endocrine clinic of Ekiti State University Teaching Hospital (EKSUTH), Ado-Ekiti, between October to December 2018. Demographic information such as age, gender, and duration of diabetes were documented in a questionnaire, while anthropometry, systolic and diastolic blood pressures (SBP & DBP) were determined. PAD, PN, and IR were determined by ankle brachial index (ABI), vibration perception threshold (VPT) to biothesiometer and homeostasis model (HOMA2-IR) respectively. Association among variables of interest were determined with Pearson’s Chi-Square, Student’s t test, and Pearson’s correlation. There were 90 participants, with a mean age of 58.7(11.6) years. The prevalence of PAD was 40% (37.0% in men and 40.7% in women, p =0.36), and 12.2% had moderate PAD. Compared to patients without PAD, those with PAD had higher mean HOMA2-IR (3.71 vs 2.01, p<0.001), glycosylated haemoglobin (HbAic) (9.4% vs 7.7%, p=0.004), and SBP (135.6mmHg vs 126.9mmHg, p=0.025), and more likely to have PN (67.7% vs 26.7%, p<0.001. ABI negatively correlated with HOMA2-IR (r=-0.403, p<0.001), HbAic (r= -0.347, p=0.001), SBP(r=-0. 391, p<0.001), DBP (r=-0.22, p=0.037), and duration of diabetes (r=-0.251, p=0.042). Peripheral arterial disease (PAD) was more prevalent among T2DM patients with neuropathy.Insulin resistance positively correlated with vibration perception threshold. All diabetic patients with PN should be screened for PAD.